Onset of sexual maturity and relative growth of the freshwater crab Trichodactylus fluviatilis (Trichodactyloidea) in south-eastern Brazil - Lima, Daniel José Marcondes [UNESP]; Cobo, Valter José [UNESP]; Alves, Douglas Fernandes Rodrigues [UNESP]; Barros-Alves, Samara de Paiva [UNESP]; Fransozo, Vivian [UNESP] (Taylor & Francis, 2013)
The main purpose of this study was to provide an estimate for the onset of morphological sexual maturity in the freshwater crab Trichodactylus fluviatilis, from a population located in south-eastern Brazil, based on the relative growth relationships, as well as the characterization of ''handedness''. Monthly collections were carried out at night, from January 2006 to January 2007, in a small water body. In the laboratory, the crabs were sexed; the following body structures were measured and the estimate of onset of sexual maturity was given by the logistic function, as y a/(1\+becx), for 50% of the population to reach the adult phase (CW50carapace width). Right propodus length and abdomen width were the best-fit relationships to represent the onset of sexual maturity for males and females, respectively. Based on the logistic function, the onset of sexual maturity was estimated to occur at around 18mm CW for both sexes. The relative growth recorded for this species is consistent with the model for brachyuran crabs (Hartnoll RG. 1982, Growth. In: Bliss, DE, editor. The biology of Crustacea: embryology, morphology and genetics. New York: Academic Press. p. 111-196), except for the abdomen growth, which is likely to be an adaptive condition related to protection of the newly hatched young. © 2013 Taylor & Francis.
Keywords: Epimorphic development; Reproduction; Trichodactyloidea